Health service providers' views on barriers and drivers to childhood vaccination of FDMN/Rohingya refugees: a qualitative study in Cox's Bazar, Bangladesh - Reda, Sarah; Weishaar, Heide; Akhter, Sadika; Karo, Basel; Martínez, Jorge; Singh, Aarti; Jackson, Cath (Frontiers in Public Health, 2024)
Background: Despite established vaccination programs, vaccine-preventable diseases persist among about 900,000 Forcibly Displaced Myanmar Nationals (FDMN)/Rohingya refugees in the world's largest refugee settlement in Bangladesh. Health service providers (HSPs) play a key role in the delivery of childhood vaccination programs. This study explored their views on individual and context barriers and drivers to childhood vaccination in this setting. Methods: Informed by the theoretical framework of the Capability-Opportunity-Motivation-Behaviour (COM-B) model for behaviour change, this qualitative study collected data through eight focus group discussions (FGDs) with community health workers (CHWs) and vaccinators in selected camps with high or low vaccination coverage rates, and through 11 in-depth interviews (IDIs) with key informants working in strategic, management and administrative roles.Findings: Barriers and drivers were evident across all COM factors for HSPs and caregivers. Among HSPs, knowledge around vaccination acted both as a barrier and driver, while communication skills and confidence in vaccination served as drivers. Caregivers' lack of awareness of vaccination, concerns and mistrust were described as main barriers. Context barriers included information system deficiencies, family dynamics, HSPs' working conditions, and vaccination site accessibility. Context drivers included effective communication, mobilization, and incentives. Differences between high and low coverage camps in Cox's Bazar included variations in HSPs' knowledge, communication strategies, incentive use, and stakeholder collaboration.Discussion: For better vaccination coverage in the camps, context-related changes regarding collaboration, health workforce and the use of incentives seem necessary. Caregivers' mistrust towards vaccination needs to be considered under the social and historical background of the Rohingya community, and further addressed with targeted communication and campaigning.